Impact of Modern Technologies on the Guest Relation in 5-Star Hotels (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The hospitality sector is undergoing rapid digital transformation, particularly in the luxury segment  where delivering superior guest experiences is crucial. Modern technologies now serve as both operational enablers  and key drivers of guest satisfaction. Objective: This study assessed the impact of technology on guest relations in  five-star hotels by examining employee and guest perspectives. Methodology: A descriptive cross-sectional design  was used. Non probability sampling was done. Data was collected from 45 hotel employees and 55 guests in the  Delhi NCR region through structured questionnaires. Responses were analyzed using descriptive statistics. Results:  Findings indicate high adoption of digital tools, with 81% of employees reporting consistent use for guest interactions  and 98% confirming improved personalization. Email (44%) and telephone (40%) were the most common modes of  communication, while mobile check-in was used by 72% of guests. Overall, 80% of guests agreed that technology  enhanced satisfaction, though 63% preferred a hybrid model that combined digital and face-to-face service. Notably,  83% of employees reported experiencing operational challenges, compared to only 27% of guests, suggesting that staff  often shield guests from technical issues. Conclusion: Technology has become integral to guest relations in five-star  hotels, enhancing efficiency and satisfaction. However, the human touch remains essential. Continuous staff training  and system reliability are recommended to support a balanced high-tech, high-touch approach.
Keywords: Hospitality technology; guest relations; five-star hotels; customer satisfaction; hotel management; digital transformation